Supporting the use of theory in cross-country health services research: a participatory qualitative approach using Normalisation Process Theory as an example. Issue 8 (21st August 2017) - O'Donnell, Catherine A; Mair, Frances S; Dowrick, Christopher; Brún, Mary O'Reilly-de; Brún, Tomas de; Burns, Nicola; Lionis, Christos; Saridaki, Aristoula; Papadakaki, Maria; Muijsenbergh, Maria van den; Weel-Baumgarten, Evelyn van; Gravenhorst, Katja; et al.
Abstract : Objectives: To describe and reflect on the process of designing and delivering a training programme supporting the use of theory, in this case Normalisation Process Theory (NPT), in a multisite cross-country health services research study. Design: Participatory research approach using qualitative methods. Setting: Six European primary care settings involving research teams from Austria, England, Greece, Ireland, The Netherlands and Scotland. Participants: RESTORE research team consisting of 8 project applicants, all senior primary care academics, and 10 researchers. Professional backgrounds included general practitioners/family doctors, social/cultural anthropologists, sociologists and health services/primary care researchers. Primary outcome measures: Views of all research team members (n=18) were assessed using qualitative evaluation methods, analysed qualitatively by the trainers after each session. Results: Most of the team had no experience of using NPT and many had not applied theory to prospective, qualitative research projects. Early training proved didactic and overloaded participants with information. Drawing on RESTORE's methodological approach of Participatory Learning and Action, workshops using role play, experiential interactive exercises and light-hearted examples not directly related to the study subject matter were developed. Evaluation showed the study team quickly grew in knowledge and confidence in applying theory to fieldwork. Recommendations applicable to other studies include: accepting that theory application is not a linear process, that time is needed to address researcher concerns with the process, and that experiential, interactive learning is a key device in building conceptual and practical knowledge. An unanticipated benefit was the smooth transition to cross-country qualitative coding of study data. Conclusion: A structured programme of training enhanced and supported the prospective application of a theory, NPT, to our work but raised challenges. These were not unique to NPT but could arise with the application of any theory, especially in large multisite, international projects. The lessons learnt are applicable to other theoretically informed studies.